An Examination of Embryogenic and Non-Embryogenic Cultures of Oil Palm (Elaeis Guineensis Jacq.) - Ong, Li Mei (2001)
Somatic embryogenesis of crop plants such as oil palm has generated considerable research interest. However, the main obstacle that hinders the development of an economically viable propagation system is the low frequency of embryogenesis. Currently, most local tissue culture laboratories are reporting embryogenesis rates of approximately 6%. Due to the lack of knowledge about oil palm somatic embryogenesis, it would be difficult to understand or even to attempt to improve the process. Hence, this study has been tailored to understand the fundamental processes that could occur during embryogenesis by analyzing differences between embryogenic (BC) and non-embryogenic (NEC) in vitro cultures of oil palm. The initial studies concentrated on elucidating the differences found between EC and NEC at the microscopical level. Proembryo (PE) structures were predominantly found in ECs. The phenomenon of isolation of cells, as a prerequisite to embryogenesis, was observed in the formation of PEs. It was hypothesized that the surrounding cells at the periphery of each PE structure could have gone through programmed cell death (PCD) hence creating the condition of 'isolation of cells'.The hypothesis that PCD could play an important role in the embryogenesis process was further supported by studies carried out at the physiological and molecular level. ECs were found to be metabolically more active than NECs, thus indicating that ECs would need an efficient system to overcome the accumulation of reactive oxygen species (ROS), a toxic byproduct of aerobic metabolism. With the isolation of the embryogenic tissue specific OPEml, which encodes for an antioxidant known as peroxiredoxin, it is believed that it functions by protecting the proembryos from being damaged by the ROS but killing the cells surrounding them. OPEml represents the first peroxiredoxin to be isolated from a palm and has potential to be exploited as a molecular marker for embryogenic potential of in vitro cultures. In addition to this, with the knowledge of the physiological state of embryogenic and non-embryogenic cultures, a non-destructive method for the detection of embryogenic potential can now be devised by taking advantage of the reaction mechanism of oxidative dyes in culture media.Besides this, attempts were also made to isolate other embryogenic related genes by means of a rapid cloning method for differentially expressed cDNAs. This technique is better known as Suppression Subtractive Hybridization. Out of a total 595 clones screened, only 66 were found to be embryogenic specific. Amongst these clones, one of them was characterized and shown to be closely related to a class IV chitinase EP3. This clone was designated as OPSSHI. There is some evidence to suggest from the northern analysis study, that different subsets of class IV endochitinase EP3 were being detected, as two differently sized transcripts were observed. It is possible that they encode proteins that have differing functions. However, due to the generally short fragments being produced through this technique, it is still too early to propose a functional role for endochitinase(s) in the oil palm system.